Animasi sebagai Media Pembelajaran Kreatif dalam Mata Pelajaran Bimbingan Konseling - Atmojo, Ignatius Rezha; Aditya, Made Wira (Magenta | Official Journal STMK Trisakti, 2018)
Counseling guidance materials that are generally theoretical are often less interesting and saturating for learners. The learners tend to get bored easily by teaching teachers who only use lecture methods and explain on the board without any interaction. Some of today's learner are more happy to play mobile when the teacher taught in the appeal to listen to her teacher. Looking at the above conditions, Then the counseling teachers can use animation media to deliver learning materials in an interesting and interactive so that learning materials can be communicated and understood well by learners. Case examples on counseling material can be visualized attractively through the image and color display of the animation.